2019
DOI: 10.5765/jkacap.190019
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health of Ethnic Minority Youths in South Korea and Its Related Environmental Factors: A Literature Review

Abstract: Objectives: With increasing concerns for the rapidly growing minority population in South Korea, this literature review addressed a range of mental health risks among multiethnic youths (MY) in South Korea by 1) comparing mental health outcomes with those of native-born youths and 2) identifying multiple layers of relevant environmental factors, from family and school relationships to culture. Methods: We reviewed 54 studies that fulfilled specific inclusion criteria. Results: Multiple common risk/protective f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…This phenomenon is more prominent among adolescents belonging to multicultural families. A literature review reported that 115 Korean adolescents and 795 of those from multicultural families were more likely to engage in delinquency, violence, and game addictions; furthermore, it was revealed that 3995 Korean multicultural adolescents had a higher tendency to engage in substance abuse than monocultural adolescents in South Korea [ 5 ]. Additionally, 881 Mexican adolescents from multicultural families’ experienced higher stress levels, due to internal conflicts over bicultural adjustment and having parents belonging to different nationalities and cultures [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is more prominent among adolescents belonging to multicultural families. A literature review reported that 115 Korean adolescents and 795 of those from multicultural families were more likely to engage in delinquency, violence, and game addictions; furthermore, it was revealed that 3995 Korean multicultural adolescents had a higher tendency to engage in substance abuse than monocultural adolescents in South Korea [ 5 ]. Additionally, 881 Mexican adolescents from multicultural families’ experienced higher stress levels, due to internal conflicts over bicultural adjustment and having parents belonging to different nationalities and cultures [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is an accumulated evidence showing that MA living in Korea have low life satisfaction and high depression, but there is still a lack of research on how to promote their health. Compared to other native Korean adolescents, MA living in Korea experience psychological problems due to socioeconomic factors (nationality and education level of their parents), family factors (parenting, relationship quality), social factors (discrimination), cultural factors (acculturative stress and bicultural acceptance) (Lee et al, 2019). Most existing studies conducted on MA explain depression and life satisfaction as one point and moving in one direction (Cho & Park, 2020;Zadow et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…AMFs are likely to face prejudice and discrimination, which are still prevalent in Korean society but an earlier study of Joo et al (42) showed that the perceived support of Chinese Koreans from family and meaningful others decreased the perception of acculturative stress. Therefore, an approach that improves social support from peer, teachers, or family for AMFs will be important in that mental health problems such as depression and anxiety can be triggered when acculturative stress is high (43,44). However, as acculturative stress had a mediating role in the relationship between social support and health outcomes (42), a future study is needed to confirm the mediating effect of acculturative stress on the relationship between social support and well-being in AMFs.…”
Section: Discussionmentioning
confidence: 99%